Decentralization as a policy to promote community participation in the development of Rwanda : a case study of the Nyarugenge district - Grobbelaar, Janis (University of Pretoria, 2013)
Mini Dissertation (MSocSci (Industrial Sociology and Labour Studies))--University of Pretoria, 2006.